Pengembangan Media Pembelajaran Virtual dan Interaktif Untuk Mensimulasikan Instalasi Jaringan Listrik di SMK 2 Surakarta - Joko Susilo; Asrowi Asrowi; Sri Anitah (Universitas Sebelas Maret, 2018)
The learning of electrical installation at Vocational High School often comes to problems as the availability of real apparatus or equipment which are not used again on the next period. It is also getting worse as the learning style is not effective by that way in a group. When it is done in a group, certain student will rely on his/her work to other friends. Consequently, they will get no beneficial from the instructional process done. Therefore, it is developed an interactive multimedia of simple electrical series in order to be directly tried by each student easily. At last, they will be motivated and get the benefit from the lesson